(untitled) (Fiep Bulletin - online, 2011)
This study had as objective to evaluate the school performance of remaining children of quilombolas. 145 students of the first segment of basic education (1st to 4th level) of Quilombola communities, 55 girls and 90 boys, participated in the process. The Test of School Performance was used to evaluate the basic skills for writing, arithmetic and reading, classifying them into superior, medium and inferior. The results showed significant difference showing that the lowest performance was verified for males and for the fourth level of basic teaching. We can conclude that studies about the difficulty of learning should be widened, once its incidence, independently from causes, is very high and its presence causes damages to the child, to the family, to the educational system, to the country and to the professionals who work with education.